(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article discusses the pedagogical foundations, practical possibilities, and effectiveness of working with students on the basis of an individual and differentiated approach in teaching computer science. The research uses a mixed-methods approach — a combination of qualitative and quantitative analysis methods — to study the experience of teachers, their approaches to the lesson process, and their impact on students’ knowledge, motivation, and creative activity. The results show that individual and differentiated approaches are an important tool for improving the quality of computer science education, guiding students on a personal development trajectory, and effectively integrating modern technologies. At the end of the article, methodological recommendations for computer science teachers are developed.